Molecular Mechanisms of Lithium Action: Switching the Light on Multiple Targets for Dementia Using Animal Models - Kerr, Fiona; Bjedov, Ivana; Sofola-Adesakin, Oyinkan (Frontiers in Molecular Neuroscience, 2018)
Lithium has long been used for the treatment of psychiatric disorders, due to its robust beneficial effect as a mood stabilising drug. Lithium’s effectiveness for improving neurological function is therefore well-described, stimulating the investigation of its potential use in several neurodegenerative conditions including Alzheimer’s (AD), Parkinson’s (PD) and Huntington’s (HD) diseases. A narrow therapeutic window for these effects, however, has led to concerted efforts to understand the molecular mechanisms of lithium action in the brain, in order to develop more selective treatments that harness its neuroprotective potential whilst limiting contraindications. Animal models have proven pivotal in these studies, with lithium displaying advantageous effects on behaviour across species, including worms (C.elegans), zebrafish (Danio Rerio), fruit flies (Drosophila melanogaster) and rodents. Due to their susceptibility to genetic manipulation, functional genomic analyses in these model organisms have provided evidence for the main molecular determinants of lithium action, including inhibition of inositol monophosphatase (IMPA) and glycogen synthase kinase-3 (GSK-3). Accumulating pre-clinical evidence has indeed provided a basis for research into the therapeutic use of lithium for the treatment of dementia, an area of medical priority due to its increasing global impact and lack of disease-modifying drugs. Although lithium has been extensively described to prevent AD-associated amyloid and tau pathologies, this review will focus discussion on generic mechanisms by which lithium preserves neuronal function and improves memory in animal models of dementia. Of these, evidence from worms, flies and mice points to GSK-3 as the most robust mediator of lithium’s neuro-protective effect, but it’s interaction with downstream pathways, including Wnt/β-catenin, CREB/BDNF, Nrf2 and TLR4/NFкB, have identified multiple targets for development of drugs which harness lithium’s neurogenic, cytoprotective, synaptic maintenance, anti-oxidant, anti-inflammatory, and protein homeostasis properties, in addition to more potent and selective GSK-3 inhibitors. Lithium, therefore, has advantages as a multi-functional therapy to combat the complex molecular pathology of dementia. Animal studies will be vital, however, for comparative analyses to determine which of these defence mechanisms are most required to slow-down cognitive decline in dementia, and whether combination therapies can synergise systems to exploit lithium’s neuro-protective power while avoiding deleterious toxicity.